Influence of Beam-to-Column Linear Stiffness Ratio on Failure Mechanism of Reinforced Concrete Moment-Resisting Frame Structures - Jizhi Su; Boquan Liu; Guohua Xing; Yudong Ma; Jiao Huang (Advances in Civil Engineering)
The design philosophy of a strong-column weak-beam (SCWB), commonly used in seismic design codes for reinforced concrete (RC) moment-resisting frame structures, permits plastic deformation in beams while keeping columns elastic. SCWB frames are designed according to beam-to-column flexural capacity ratio requirements in order to ensure the beam-hinge mechanism during large earthquakes and without considering the influence of the beam-to-column stiffness ratio on the failure modes of global structures. The beam-to-column linear stiffness ratio is a comprehensive indicator of flexural stiffness, story height, and span. This study proposes limit values for different aseismic grades based on a governing equation deduced from the perspective of member ductility. The mathematical expression shows that the structural yielding mechanism strongly depends on parameters such as material strength, section size, reinforcement ratio, and axial compression ratio. The beam-hinge mechanism can be achieved if the actual beam-to-column linear stiffness ratio is smaller than the recommended limit values. Two 1/3-scale models of 3-bay, 3-story RC frames were constructed and tested under low reversed cyclic loading to verify the theoretical analysis and investigate the influence of the beam-to-column linear stiffness ratio on the structural failure patterns. A series of nonlinear dynamic analyses were conducted on the numerical models, both nonconforming and conforming to the beam-to-column linear stiffness ratio limit values. The test results indicated that seismic damage tends to occur at the columns in structures with larger beam-to-column linear stiffness ratios, which inhibits the energy dissipation. The dynamic analysis suggests that considering the beam-to-column linear stiffness ratio during the design of structures leads to a transition from a column-hinge mechanism to a beam-hinge mechanism.